Low-frequency electroacupuncture attenuates methamphetamine-induced depressive-like behaviors and cognitive impairment via modulating neuroinflammation - Zhang, Jingyi; Hui, Rongji; Xu, Jiabao; Zhang, Ludi; Xie, Bing; Ma, Chunling; Li, Yi; Zou, Yueli; Wen, Di; Yu, Xiujun (Frontiers in Neurology, 2025)
IntroductionMethamphetamine (METH) abuse primarily affects the central nervous system (CNS), leading to CNS damage and contributing to depressive-like behaviors, cognitive impairment, and other neuropsychiatric disorders. Electroacupuncture (EA) has shown promise in treating mental disorders linked to CNS damage, yet the effects of EA on METH-induced depressive-like behaviors and cognitive impairment and it’s underlying therapeutic mechanisms remain largely unclear.MethodsIn this study, a mouse model of METH-induced neuropsychiatric dysfunction was established by administering high-dose METH under elevated ambient temperature. EA was applied at different frequencies to the Zusanli (ST36) acupoint for 7 days post-METH administration.ResultsBehavioral tests revealed that low-frequency EA significantly alleviated depressive-like behaviors and cognitive impairment. Additionally, EA restored blood-brain barrier (BBB) integrity, as evidenced by Western blotting (WB) and Evans blue staining. Neuronal injury was attenuated, as shown by Nissl and hematoxylin and eosin (HE) staining. Further investigations into neuroinflammation revealed that EA suppressed microglial activation in the hippocampus, decreased the expression of IL-6 and TNF-α, and inhibited the NF-κB/NLRP3 signaling pathway.DiscussionThe present study suggested that EA alleviates METH-induced depressive-like behaviors and cognitive impairment by modulating neuroinflammation, particularly through the inhibition of microglial activation and pro-inflammatory cytokine release. EA may represent a promising non-pharmacological strategy for the treatment of METH-associated neuropsychiatric disorders.